Loss of ZNF148 enhances insulin secretion in human pancreatic β cells - Eleonora de Klerk; Yini Xiao; Christopher H. Emfinger; Mark P. Keller; David I. Berrios; Valentina Loconte; Axel A. Ekman; Kate L. White; Rebecca L. Cardone; Richard G. Kibbey; Alan D. Attie; Matthias Hebrok (JCI Insight, 2023)
Insulin secretion from pancreatic β cells is essential to the maintenance of glucose homeostasis. Defects in this process result in diabetes. Identifying genetic regulators that impair insulin secretion is crucial for the identification of novel therapeutic targets. Here, we show that reduction of ZNF148 in human islets, and its deletion in stem cell–derived β cells (SC–β cells), enhances insulin secretion. Transcriptomics of ZNF148-deficient SC–β cells identifies increased expression of annexin and S100 genes whose proteins form tetrameric complexes involved in regulation of insulin vesicle trafficking and exocytosis. ZNF148 in SC–β cells prevents translocation of annexin A2 from the nucleus to its functional place at the cell membrane via direct repression of S100A16 expression. These findings point to ZNF148 as a regulator of annexin-S100 complexes in human β cells and suggest that suppression of ZNF148 may provide a novel therapeutic strategy to enhance insulin secretion.